ENTREPRENEURIAL FACTORS AND SOCIAL MEDIA ENGAGEMENT AS DRIVERS OF COFFEE SHOP SUCCESS IN JAKARTA - Patrick Bennet Julius; Lydiawati Soelaiman (Graduate Program of Universitas Tarumanagara, 2026)
The growth of local coffee shop industries in Jakarta reflects a highly competitive dynamic, driven by increasing coffee consumption and shifting urban lifestyles. This research seeks to explore the influence of motivation, entrepreneurial skills, entrepreneurial knowledge, and the use of social media on the entrepreneurial success of local coffee shops in Jakarta. Quantitative methods were applied by means of the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, involving 95 local coffee shop entrepreneurs obtained by means of purposive sampling. The evidence suggests that all independent the aggregate determinants elucidate 82.3% regarding the dispersion observed in entrepreneurial success. Furthermore, findings from the hypothesis analyses suggest that motivation, entrepreneurial skills, entrepreneurial knowledge, and use of social media each positively and significantly affect the success of local coffee shops in Jakarta. These findings underscore that combining internal entrepreneurial factors and the strategic use of social media shapes entrepreneurial success. The implications derived from this research emphasize the critical role of strengthening entrepreneurial capacity and leveraging social media to enhance competitiveness and ensure business sustainability.